2004
DOI: 10.1097/01.blo.0000143560.41767.ee
|View full text |Cite
|
Sign up to set email alerts
|

Biology of Developmental and Regenerative Skeletogenesis

Abstract: Embryonic skeletal development involves the recruitment, commitment, differentiation, and maturation of mesenchymal cells into those in the skeletal tissue lineage, specifically cartilage and bone along the intramembranous and endochondral ossification pathways. The exquisite control of skeletal development is regulated at the level of gene transcription, cellular signaling, cell-cell and cell-matrix interactions, as well as systemic modulation. Mediators include transcription factors, growth factors, cytokine… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
81
0
4

Year Published

2006
2006
2019
2019

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 104 publications
(86 citation statements)
references
References 111 publications
1
81
0
4
Order By: Relevance
“…RT was performed with SuperScript III (Invitrogen) and an oligo(dT) [12][13][14][15][16][17][18] primer. Four microliters of RNA was added into a final volume of 21-l solution containing 10 mM dNTP mix, 10ϫ RT buffer, 25 mM MgCl 2 , 0.1M dithiothreitol, RNase inhibitor, and RNase H. Six microliters of RT product was used for the amplification reaction in a final volume of 50 l, containing 2.5 mM dNTP, 25 mM MgCl 2 , primers specific for each gene (for SOX9, primer 1 [P1] GGCAGCTGTGAACT-GGCCA, and P2 GCACACGGGGAACTTGTCC; for COL2A1, P1 CACGCAGAAGTTCACCAAGAA, and P2 CCTTGCTCCAGGGCCAGC; for aggrecan, P1 TGAG-GAGGGCTGGAACAAGTACC, and P2 GGAGGTGGTA-ATTGCAGGGAACA; for RUNX2, P1 ACCATGGTG-GAGATCATCGC, and P2 CATCAAGCTTCTGTCTGTGC; for ALP, P1 ACGTGGCTAAGAATGTCATC, and P2 CTG-GTAGGCGATGTCCTTA; for osteocalcin, P1 CAT-GAGAGCCCTCACA, and P2 AGAGCGACACCCTAGAC; for osteopontin, P1 CAGAATCTCCTAGCCCCACA, and P2 AACTCCTCGCTTTCCATGTG; and for GAPDH, P1 GCTCTCCAGAACATCATCCCTGCC, and P2 CGTTGT-CATACCAGGAAATGAGCTT), and Taq DNA polymerase (Invitrogen).…”
Section: Rna Extraction and Reverse Transcription-polymerase Chain Rementioning
confidence: 99%
See 2 more Smart Citations
“…RT was performed with SuperScript III (Invitrogen) and an oligo(dT) [12][13][14][15][16][17][18] primer. Four microliters of RNA was added into a final volume of 21-l solution containing 10 mM dNTP mix, 10ϫ RT buffer, 25 mM MgCl 2 , 0.1M dithiothreitol, RNase inhibitor, and RNase H. Six microliters of RT product was used for the amplification reaction in a final volume of 50 l, containing 2.5 mM dNTP, 25 mM MgCl 2 , primers specific for each gene (for SOX9, primer 1 [P1] GGCAGCTGTGAACT-GGCCA, and P2 GCACACGGGGAACTTGTCC; for COL2A1, P1 CACGCAGAAGTTCACCAAGAA, and P2 CCTTGCTCCAGGGCCAGC; for aggrecan, P1 TGAG-GAGGGCTGGAACAAGTACC, and P2 GGAGGTGGTA-ATTGCAGGGAACA; for RUNX2, P1 ACCATGGTG-GAGATCATCGC, and P2 CATCAAGCTTCTGTCTGTGC; for ALP, P1 ACGTGGCTAAGAATGTCATC, and P2 CTG-GTAGGCGATGTCCTTA; for osteocalcin, P1 CAT-GAGAGCCCTCACA, and P2 AGAGCGACACCCTAGAC; for osteopontin, P1 CAGAATCTCCTAGCCCCACA, and P2 AACTCCTCGCTTTCCATGTG; and for GAPDH, P1 GCTCTCCAGAACATCATCCCTGCC, and P2 CGTTGT-CATACCAGGAAATGAGCTT), and Taq DNA polymerase (Invitrogen).…”
Section: Rna Extraction and Reverse Transcription-polymerase Chain Rementioning
confidence: 99%
“…MSCs with the capacity to differentiate into the mesenchymal lineage can be isolated from the bone marrow (10)(11)(12), fat tissue (11), umbilical cord blood (13), and amniotic fluid (14). It has been reported that the chondrogenic abilities of MSCs could be triggered with various growth factors, including transforming growth factor ␤ (TGF␤) and fibroblast growth factor (FGF) (15,16).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Conceptually, postnatal skeletal maturation in mammals may be considered an ex utero extension of a developmental process begun early in embryonic life (Tuan, 2004;Provot and Schipani, 2005). From the onset of chondrogenesis in the developing limb bud, the processes of endochondral elongation and endochondral ossification proceed along a nearly exponential trajectory (Goldring et al, 2006).…”
mentioning
confidence: 99%
“…The initial driving force for the application of BMPs to promote cartilage and bone formation arose from the original study by Urist (8), who showed that demineralized bone implanted subcutaneously in muscle resulted in the formation of endochondral bone. Following the pioneering studies of Friedenstein and colleagues (9), who identified bone-forming progenitor cells from rat bone marrow, the capacity of MSCs to differentiate into cartilage, fat, and muscle cells, as well as bone cells, was established (10)(11)(12).…”
Section: Mary B Goldringmentioning
confidence: 99%